COMMUNITY DEVELOPMENT THROUGH THE USE OF PLASTIC WASTE MANAGEMENT AS HYDROPONIC - Rukun Santoso; Alfian Bachtiar; Nurhayati Nurhayati; Ita Erliyani; Afif Alfiyanto (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Community service activities are community service activities in certain areas as an implementation of higher education. Service activities aim to provide field experience to researchers about community conditions and form an independent attitude and responsibility in carrying out service activities. The service implementation during the Covid-19 Pandemic starts from June 15 to July 24, 2020, in Eight Ulu Village, Jakabaring District, Palembang. Service activities are empowering and processing plastic waste for hydroponic manufacturing, beautifying the home page and improving the surrounding community's economy by selling the results of growing vegetables on Hydroponics. Community service activities in Kelurahan Delapan Ulu, Jakabaring District, Palembang, went well because the community response was also good. The implementation of this service is expected to benefit the community, especially in Kelurahan Delapan Ulu Palembang.